The Social Construction of Commercial Law: How Cultural Values Shape Business Regulations - MW Lasut, Meiske; Mesra, Romi (PT. NALURI EDUKASI PRESS, 2024)
This research examines how cultural values influence the development and structure of commercial law across different societies, addressing the critical question of whether business regulations simply reflect technical economic requirements or embody deeper cultural values about appropriate commercial conduct. The study employs a qualitative methodology based on systematic literature review, analyzing over 200 academic sources from multiple disciplines including law, sociology, anthropology, and economics to identify patterns in how cultural values shape commercial law development. The research utilizes thematic analysis to examine cultural transmission mechanisms and contemporary challenges in cultural-legal interactions within commercial regulatory frameworks. The findings reveal that cultural values serve as fundamental determinants of commercial law structure, influencing property rights concepts, corporate governance frameworks, and regulatory enforcement mechanisms across different societies. The research identifies specific cultural transmission mechanisms including legal education institutions, judicial decision-making processes, professional organizations, and international legal transplantation that embed cultural values within commercial law systems. Contemporary challenges including globalization, digital transformation, and environmental governance create new tensions between universal commercial law principles and culturally specific regulatory approaches. The study concludes that cultural values continue to play a persistent and fundamental role in shaping commercial law development, requiring greater sensitivity to cultural diversity in international commercial regulation and legal harmonization efforts.